THE EFFECT OF SELF-CONFIDENCE ON THE MATHEMATICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Ratri Rahayu; Henry Suryo Bintoro; Alif Catur Murti (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
AbstractMathematical thinking ability is the ability to use reasoning to build mathematical arguments, the ability to develop strategies or methods, understand mathematical content, and the ability to communicate ideas. The mathematical thinking ability as a learning goal and at the same time as a way to learn mathematics is an important ability to be developed in solving problems. One of the factors that influence students' mathematical thinking ability is self-confidence. The purpose of this study was to analyze the effect of self-confidence on students' mathematical thinking ability. This research is quantitative research. The sample in this study was 72 students of VIIth grade junior high school students in Kudus Regency, Indonesia. The data collection technique consisted of a written test of mathematical thinking ability and a self-confidence questionnaire. The data analysis technique is a simple linear regression test. Based on the results of the study showed that self-confidence has a positive and significant effect of 25.5% on mathematical thinking ability. AbstrakKemampuan berpikir matematis adalah kemampuan menggunakan penalaran untuk membangun argumen matematis, kemampuan mengembangkan strategi atau metode, memahami isi matematis, dan kemampuan mengomunikasikan gagasan. Kemampuan berpikir matematis sebagai tujuan pembelajaran dan sekaligus sebagai cara belajar matematika merupakan kemampuan yang penting untuk dikembangkan dalam memecahkan masalah. Salah satu faktor yang mempengaruhi kemampuan berpikir matematis siswa adalah rasa percaya diri. Tujuan penelitian ini adalah untuk menganalisis pengaruh kepercayaan diri terhadap kemampuan berpikir matematis siswa. Penelitian ini merupakan penelitian kuantitatif. Sampel dalam penelitian ini adalah 72 siswa kelas VII SMP di Kabupaten Kudus, Indonesia. Teknik pengumpulan data terdiri dari tes tertulis kemampuan berpikir matematis dan angket kepercayaan diri. Teknik analisis data yang digunakan adalah uji regresi linier sederhana. Berdasarkan hasil penelitian menunjukkan bahwa kepercayaan diri berpengaruh positif dan signifikan sebesar 25,5% terhadap kemampuan berpikir matematis.